The Development of A “Literang” Instrument to Measure Coral Reef Literacy - Rizkia, Rinjani Ayu; Suryanda, Ade; Komala, Ratna (Bioeducation Journal, 2024)
Coral reefs are one of the protected species in the marine ecosystem which acts as a provider of shelter for other marine biota. Until now, coral reefs have received special attention because their health conditions are threatened. Coral reef literacy is one of the important efforts that we as educated students have, to play a role in efforts to protect and preserve coral reef ecosystems. Therefore, this Coral Reef Literacy Instrument was developed to measure coral reef literacy skills. The aim of this study was to develop instruments to measure coral reef literacy abilities. The method in this study is a research and development method using the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The subjects of this study were students of the Faculty of Education, State University of Jakarta. Overall, the feasibility of the instrument by two material experts and one linguist was 83.5%, this indicated that the coral reef literacy instrument was stated to be very feasible to use to measure coral reef literacy abilities.